Modeling Dike Failure using the Material Point Method. (2017) - Martinelli, Mario; Rohe, Alexander; Soga, Kenichi
Abstract: In this study, the material point method (MPM) is used to simulate and analyze the onset and evolution of the failure of a sand dike due to seepage flow. To that purpose, a MPM formulation in conjunction with an elastic-perfectly plastic soil model with Mohr-Coulomb failure criterion is used. For comparison, the onset of failure is also simulated with the standard finite element method. The results show that the double-point MPM formulation can satisfactorily model the essential features of the failure mechanism of the dike.